Evaluation of the effect of Sidoarjo mud on aquatic life using chromatophores and the microstructure of fish scales - Hidayati, Dewi; Norela Sulaiman,; B.S. Ismail,; Mohammad Shuhaimi Othman,; Bellard, Maria Elena de (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Sidoarjo mud is the first visible phenomenon of a mud volcano that occurs in a human settlement and which is subsequently channelled into a river. Clay, aluminium and iron were reported to be the dominant contaminants that could possibly come into contact with and accumulate on the surface of local fish and initiate alteration in scale microstructure. The aim of this study was to evaluate the extent of water body contamination in the Sidoarjo mud by evaluating the chromatophore density and microstructure deformation of fish scales that act as biomarkers. Scale samples were obtained from caged Mozambique tilapia (Oreochromis mossambicus) fish that were placed downstream and upstream of the Sidoarjo mud spillway pipes. With respect to melanophore density, it was found that the scales of fish exposed in the downstream section were significantly lower in chromatophores (<50 chr/mm²) than the control scales in fish from the upstream station (>100 chr/mm²). This study suggested that the density of chromatophores was closely related to the concentration of total suspended solids (r = 0.69), which was possibly enhanced by iron (r = 0.56). Using scanning electron microscopy analysis, some deformation, i.e. irregularity of spherule shape and increasing pits in the space between ridges, were observed.